2012
DOI: 10.1016/j.ijgo.2012.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing acceptance of human papillomavirus vaccine among young female college students in Thailand

Abstract: Understanding variables associated with acceptance of HPV vaccination may guide immunization initiatives and so increase the uptake rate among young Thai women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Nineteen percent of the female college students in our study had engaged in sexual intercourse with an average age of 18.45 for their sexual debut. This percentage was less than that in many Western countries such as the United States (US) (78%), France (67.2%), Italy (45.5%) [14,15,16] but similar to that in other Asian countries [15,17,18]; however, the overall prevalence of HPV in Taiwan could be as high as 19.85%, and the younger the subjects, the higher the infection and multiple infection rates [19]. Only 9.5% of our participants were vaccinated.…”
Section: Discussionmentioning
confidence: 63%
“…Nineteen percent of the female college students in our study had engaged in sexual intercourse with an average age of 18.45 for their sexual debut. This percentage was less than that in many Western countries such as the United States (US) (78%), France (67.2%), Italy (45.5%) [14,15,16] but similar to that in other Asian countries [15,17,18]; however, the overall prevalence of HPV in Taiwan could be as high as 19.85%, and the younger the subjects, the higher the infection and multiple infection rates [19]. Only 9.5% of our participants were vaccinated.…”
Section: Discussionmentioning
confidence: 63%
“…Though most students preferred vaccination before sexual debut, they might be unaware of current statistics regarding sexual activity among young Chinese. While an average age at sexual debut ages ranging from 17.4 to 19.8 has been reported for college-educated women in other countries (Bendik et al, 2011;Juntasopeepun et al, 2012;Makwe et al, 2012), Chinese researchers have found a trend toward the lowering of age at sexual debut . Moreover, researchers have noted a trend towards decreasing age at menarche.…”
Section: Discussionmentioning
confidence: 88%
“…This is consistent with findings from other countries in the pacific region. 25 Very few undergraduates had ever heard of HPV and HPV vaccine. A great proportion of them did not know the best age to take the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…5 The quadrivalent vaccine (Gardasil) covers HPV 6,11,16 and 18. It is efficacious in preventing many of the above mentioned morbidities in both men and women. For example, Gardasil was efficacious to prevent nearly 100% of cervical cancers among women aged [18][19][20][21][22][23][24]6 90% of genital lesions among heterosexual men aged [16][17][18][19][20][21][22][23][24][25][26]7 78% of ano-genital warts and 75% of anal intraepithelial neoplasia among MSM. 8 Its safety was also warranted in above-mentioned populations.…”
Section: Introductionmentioning
confidence: 99%